Preoperative Optimization of Crohn Disease - Sharma, Amit; Chinn, Bertram T. (Clinics in Colon and Rectal Surgery, 2013)
Crohn disease is a chronic disease that is treated with aminosalicylates, antibiotics, and immunosuppressant agents. Most patients ultimately require surgical intervention and many will require additional surgery for recurrent disease. Consequently, surgery is generally performed only when medical management fails; however, these patients are often malnourished and immunosuppressed. Preoperative optimization is necessary to minimize morbidity, including intra-abdominal septic complications and anastomotic leaks. In this article, the authors review some considerations to improve the surgical outcome in Crohn disease.
Keywords: Crohn disease; immunomodulators; biologic therapy; steroids; nutrition